Therapeutic Communalism and Intimate Partner Violence: Case Scenarios from Nigeria, the United States, and the United Kingdom - Ijiomah, Amarachukwu Onyinyechi (Universitas Negeri Makassar, 2025)
Intimate partner violence represents a pervasive global crisis affecting millions of individuals annually, with consequences extending across physical, psychological, and social dimensions. Existing responses often prioritize legalistic or individualized interventions, which, while necessary, frequently fail to address the relational, communal, and systemic roots of the problem. This article proposes Therapeutic Communalism as a relational, community based framework for preventing and addressing intimate partner violence. The framework emphasizes shared responsibility, communal care, and relational accountability, moving beyond punitive or purely therapeutic models. Using illustrative case scenarios from Nigeria, the United States, and the United Kingdom, the article demonstrates how Therapeutic Communalism can be adapted across differing social, cultural, and institutional contexts. It examines the multilevel harms of intimate partner violence affecting individuals, families, communities, and children, and underscores the imperative of public sensitization, early recognition, and communal intervention. By integrating legal frameworks with communal engagement, Therapeutic Communalism offers a scalable model for reducing violence, supporting survivors, and fostering social transformation.